Exploring the ocean for new drug developments: Marine pharmacology - Harshad Malve (Wolters Kluwer Medknow Publications, 2016)
Disease ailments are changing the patterns, and the new diseases are emerging due to changing environments. The enormous growth of world population has overburdened the existing resources for the drugs. And hence, the drug manufacturers are always on the lookout for new resources to develop effective and safe drugs for the increasing demands of the world population. Seventy-five percentage of earth's surface is covered by water but research into the pharmacology of marine organisms is limited, and most of it still remains unexplored. Marine environment represents countless and diverse resource for new drugs to combat major diseases such as cancer or malaria. It also offers an ecological resource comprising a variety of aquatic plants and animals. These aquatic organisms are screened for antibacterial, immunomodulator, anti-fungal, anti-inflammatory, anticancer, antimicrobial, neuroprotective, analgesic, and antimalarial properties. They are used for new drug developments extensively across the world. Marine pharmacology offers the scope for research on these drugs of marine origin. Few institutes in India offer such opportunities which can help us in the quest for new drugs. This is an extensive review of the drugs developed and the potential new drug candidates from marine origin along with the opportunities for research on marine derived products. It also gives the information about the institutes in India which offer marine pharmacology related courses.